A Little Boy Lost - Hudson, W. H. (William Henry), 1841-1922; Lathrop, Dorothy Pulis, 1891-1980 (Salt Lake City, UT : Project Gutenberg, 2011)
"A Little Boy Lost" by W. H. Hudson is a novel written in the early 20th century. The story revolves around a young boy named Martin, who initially lives contentedly with his family in a remote, idyllic location. However, as he grows older, his curiosity and adventurous spirit lead him to explore beyond his familiar surroundings, placing him in a series of extraordinary and sometimes perilous encounters. The opening portion of the book introduces Martin as a joyfully curious child, fascinated by the natural world around him. He is depicted in a loving home where his father, a carpenter, finds happiness in his craft, and his mother worries about Martin's adventurous nature. The narrative unfolds Martin's adventures, including his love for play and his tendency to attract trouble, such as the incident with a snake that leads to a chase. As he grows older, his explorations take him into the wilderness, where strange phenomena like the mirage entice him and lead him further from home, ultimately setting the stage for his evolution into a wanderer who confronts both the beauty and danger of the natural world. (This is an automatically generated summary.)
Release date is 2011-12-27
E-text prepared by Suzanne Shell, Jane Moss, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive/American Libraries (http://www.archive.org/details/americana)
Keywords: Fantasy literature; Boys -- Juvenile fiction; Self-reliance -- Juvenile fiction; Nature -- Juvenile fiction